Interventions to avoid pulmonary complications after lung cancer resection - Villeneuve, Patrick James (Journal of Thoracic Disease, 2018)
Surgical resection of lung cancer is the preferred treatment for early-stage disease in medically fit patients. The rates of postoperative pulmonary complications (PPCs) such as pneumonia, empyema and atelectasis are as high as 10% in contemporary series. A review of the literature was performed to identify the best evidence supporting interventions to identify, prevent and treat PPCs. The use of patient risk scores, appropriate choice of antibiotic prophylaxis, intraoperative ventilatory strategies, chest physiotherapy, sputum management and non-invasive ventilatory support were specifically discussed, as was the relevant supporting data. Recommendations to guide best practice and inform future research questions are outlined.